Integrating Minority Women’s Narratives into EFL: A Curriculum for Language and Cultural Competence - Chen, Shu-Chuan; Liu, Hsiu-Ying (PAROLE: Journal of Linguistics and Education, 2024)
This paper presents an integrated approach to English as a Foreign Language (EFL) instruction by embedding minority women’s literature within a five-week curriculum designed to promote both linguistic proficiency and intercultural competence. Grounded in Third World feminist theory, transformative learning, and postcolonial pedagogy, the module engages students in critical analysis of short fiction by Zora Neale Hurston, Alice Walker, Amy Tan, Helena María Viramontes, and Bharati Mukherjee. Each week centers on a thematic focus—memory, matrilineal heritage, diaspora, trauma, and healing—while incorporating explicit language instruction in grammar, vocabulary, discourse, and pragmatics. The curriculum also integrates the Multicultural Teaching Competency Scale (MTCS) and the Developmental Model of Intercultural Sensitivity (DMIS) as tools for assessing teacher preparedness and student growth. Through the synergy of language and literature, this study demonstrates how EFL classrooms can serve as transformative spaces where students develop not only communicative competence but also critical empathy, cultural literacy, and ethical awareness.